The dynamics of debris-flow events in Southeast Brazil - Cabral, Victor [UNESP]; Gomes Vieira Reis, Fábio Augusto [UNESP]; Queiros Veloso, Vinicius [UNESP]; Costa Basilio, Thamiris [UNESP]; dos Santos Corrêa, Claudia Vanessa [UNESP]; Zarfl, Christiane (Elsevier, 2025)
Debris flows are a significant threat in mountain areas in Southeast Brazil. Understanding their dynamics and how a catchment morphology influences an event's magnitude and associated negative impacts is, therefore, relevant. Our goal is to compare the dynamics of debris-flow events (e.g., initiation mechanism, kinematic parameters) in four catchments located in the Southeastern portion of the Serra do Mar Mountain range, highlighting their similarities and differences. We also aim at establishing a general relationship between catchment morphometry and magnitude, based on a Spearman rank correlation analysis. Field campaigns were conducted to investigate the catchments, which were further supported by the acquisition of cartographic and remote sensing data, numerical simulation using RAMMS and rainfall analysis. Our results show that the debris-flow events are characterized by an association between debris flows, debris floods and flash floods, which is directly related to the morphology of the catchments and rainfall intensity. Considering the magnitude of the debris-flow events, Relief ratio is interpreted have a more significant impact among the morphometric parameters, according to the Spearman rank correlation analysis. Moreover, the rainfall accumulated in 48 h prior to an event showed a very strong correlation with the overall magnitude, highlighting the main role that rainfall has in debris-flow initiation and associated damage. Our study highlights the main geodynamic processes that can occur in catchments at Serra do Mar and how both morphometry and rain intensity are directly related to their occurrence.
Keywords: Landslides; Magnitude; Morphometric parameters; Natural disasters; Numerical simulation